The image of Varvara Petrovna Stavrogina and the evolution of the noblewoman in Dostoevsky’s novel “Demons” - Zheng, Sicong (Litera, 2025)
The subject of this study is the literary image of Varvara Petrovna Stavrogina, one of the most complex and undervalued female characters in Fyodor Dostoevsky’s novel Demons. The research focuses on how this figure reflects the transformation of the noblewoman in 19th-century Russian literature against the backdrop of ideological, cultural, and social crisis. The object of analysis is the aristocratic female type—endowed with external authority and symbolic status but lacking internal integrity and moral influence. The article explores how Varvara Petrovna represents the decline of the old nobility, the loss of the spiritual function of femininity, and the transition to a rhetorically constructed but substantively impoverished subjectivity. Special attention is paid to her speech strategies, interactions with other characters, and compositional role as a bearer of cultural memory and a relic of a fading social order. Methodologically, the study is based on structural-semantic, discursive, and gender-cultural analysis, with elements of comparative interpretation. The scientific novelty lies in the comprehensive rethinking of Varvara Petrovna as a typologically unique figure marking the final stage in the evolution of the noblewoman in Russian literature. For the first time, she is analyzed not as a secondary character but as a structural and ideological element of Dostoevsky’s narrative, symbolizing sociocultural disintegration. Her speech ceases to function communicatively and becomes a ritualized mechanism for preserving symbolic order. As a semiotic relic and “monument” of a bygone era, the character embodies a historical-value shift in the representation of the feminine, reflecting a move from moral authority to pragmatic, formalized subjectivity. The results may be of value in gender studies, cultural analysis, and literary criticism of late 19th-century Russian prose.